Viable Nash Equilibria: An Experiment - Duk Gyoo Kim; Daehong Min; John Wooders (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper examines the usefulness of Kalai (2020)'s measure of the viability of Nash equilibrium. We experimentally study a class of participation games, which differ in the number of players, the success threshold, and the payoff to not participating. We find that Kalai's measure captures well how the viability of the everyone-participates (eP) equilibrium depends on the success threshold; the measure does not capture other elements of the game which affect the likelihood that the eP equilibrium is played.
Keywords: C00; C70; C92; D90; 330; Nash equilibrium; viability; laboratory experiments; coordination game